Riding Globalization: Bancak Salak and The Remaining Identity - Herlinda Suksmawati; Dias Pabyantara; Praja Firdaus Nuryananda (Nusantara Science and Technology Proceedings)
Globalization is believed to be the exogenous driving force that has changed many social and political changes in the last few decades. Deprived of the identity of a socio-political entity, including the people in Indonesia, is a socio-political phenomenon that has become increasingly apparent in recent developments. Supported by increasingly high internet penetration rates, this uprooted culture is even felt in rural areas. But, that does not mean that the local wisdom of Indonesian people can then be lost. Bancakan Salak is one of the cultures of Indonesian people who retain elements of local wisdom. The word "bancakan" itself means "form of gratitude" and is manifested in the form of holding a meal together. While salak is the main plantation commodity in the Galengdowo village, Wonosalam district, Jombang. Bancakan Salak becomes interesting to study when it is associated with the loss of local culture due to globalization. Therefore, this study looks at the efforts of the Galengdowo village government to preserve the culture and local wisdom in the village. This study uses a mixed approach (mixed method). The research instruments used were interviews, observation, and questionnaires to obtain primary and secondary data. With these three instruments, it is hoped that the research team will get a clear picture of the history of the Bancakan Salak and why the Bancakan Salak tradition was remade by the Galengdowo village government.